2006
DOI: 10.1007/s00011-006-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

FK506 (tacrolimus) improves lung injury through inhibition of Fas-mediated inflammation

Abstract: Tacrolimus serves as a therapeutic option for improving lung injury through inhibition of Fas-mediated inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, long-term use of tacrolimus has been reported to affect organ transplant survival adversely because its chronic administration has been associated with nephrotoxicity, diabetes, neurotoxicity, and gastrointestinal disturbances [7,8,9]. In this regard, several studies have shown tacrolimus is toxic to renal proximal tubular epithelial cells, insulin-secreting cells, and gastric and lung epithelial cells [10,11,12]. Furthermore, the excessive production of inflammatory regulators such as cyclooxygenase-2 and transforming growth factor-β has been reported to promote tacrolimus-induced glomerular and tubular cell damage [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term use of tacrolimus has been reported to affect organ transplant survival adversely because its chronic administration has been associated with nephrotoxicity, diabetes, neurotoxicity, and gastrointestinal disturbances [7,8,9]. In this regard, several studies have shown tacrolimus is toxic to renal proximal tubular epithelial cells, insulin-secreting cells, and gastric and lung epithelial cells [10,11,12]. Furthermore, the excessive production of inflammatory regulators such as cyclooxygenase-2 and transforming growth factor-β has been reported to promote tacrolimus-induced glomerular and tubular cell damage [13,14].…”
Section: Introductionmentioning
confidence: 99%